2012
DOI: 10.1590/s1806-83242012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic evaluation of the effect of composite formulation on polymerization shrinkage stress

Abstract: We compared polymerization stress in two commercial composites and three experimental composites made using camphorquinone (CQ) and/or phenylpropanedione (PPD) as photoinitiators. The internal surfaces of photoelastic resin discs with cylindrical cavities were roughened and treated with adhesive. Composites were divided into five groups: two commercial composites (Filtek Silorane and Filtek Z250) and three experimental composites with CQ/amine, CQ/PPD/amine, and PPD/amine. Composites were photopolymerized insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
0
8
0
2
Order By: Relevance
“…Teeth restored using composite resins are especially prone to this phenomenon due to stress generated within the tooth-restoration interface following resin contraction during polymerization, known as polymerization shrinkage 2 . Should the accumulated polymerization contraction stress result in tooth-composite adhesive failure [3][4] , bacterial aggregation at the disrupted tooth-restoration margin may occur resulting in microleakage and later secondary caries. Furthermore, bonding on the cervical surface of Class II composite restorations is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Teeth restored using composite resins are especially prone to this phenomenon due to stress generated within the tooth-restoration interface following resin contraction during polymerization, known as polymerization shrinkage 2 . Should the accumulated polymerization contraction stress result in tooth-composite adhesive failure [3][4] , bacterial aggregation at the disrupted tooth-restoration margin may occur resulting in microleakage and later secondary caries. Furthermore, bonding on the cervical surface of Class II composite restorations is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the insertion/light activation technique was also a bulk increment and immediate light activation for 40 s, one could infer that the C-factor had less influence on this composite, confirming its lower degree of polymerization shrinkage 6,13,18,20,27 . It is suggested that the adhesive system of P90, although leading to lower bond strength means, is not subject to the same stress at the bond interface, since there is a lower degree of volumetric shrinkage of the composite.…”
Section: Discussionmentioning
confidence: 80%
“…Polymerization shrinkage is an intrinsic property of the resin matrix 18 , which has been undesirably ascribed to problems associated with failures in posterior teeth resin composite restorations. These failures may be cohesive fracture of enamel prisms and microgap formation, with rupture of adhesive bonds and consequent withdrawal of the restorative material from the cavity walls.…”
Section: Introductionmentioning
confidence: 99%
“…It may act alone or in combination with CQ, characterizing a synergetic and simultaneous action on formation of free radicals, which could favor the performance of materials with resinous base (6), since the PPD presents maximum peak of absorption in the ultraviolet region (UV -390 nm) (7). In this way, composites with PPD as initiator tend to reach the maximum values of polymerization slower than the ones with camphorquinone, because the rate and the speed of polymerization depend on the energy density absorbed by the composite (8).…”
Section: Introductionmentioning
confidence: 99%